SPECIES COMPOSITION AND DISTRIBUTION OF SEAWEEDS AT NAI LAGOON, NINH THUAN PROVINCE - Tien, Dam Duc (Vietnam Journal of Marine Science and Technology, 2016)
This paper presents the status of species composition and distribution of seaweeds at Nai lagoon, Ninh Thuan province. From 2013 to 2014, seaweed samples from 12 sites at Nai lagoon were collected. The result shows that, there are 47 species of marine seaweeds, belonging to four phyla: Cyanophytes (Cyanophyta), Rhodophytes (Rhodophyta), Phaeophytes (Phaeophyta) and Chlorophytes (Chlorophyta). Among them, five species were classified in Cyanophyta (comprising 10.6% of total species); fifteen species in Rhodophyta (31.9%); five species in Phaeophytea (10.6%) and twenty two species in Chlorophyta (46.9%). The number of species at each site is significantly different, ranges from 3 species (site number 17) to 20 (site number 6) and average value is 11.3 species per site. The number of species in dry season is 38 and in rainy season is 39, and 32 species appear in both seasons. The coefficient index fluctuates from 0.10 (site number 11 and 17) to 0.82 (14 and 17). Among 47 species, 31 species distribute in the littoral zone and 32 species distribute in sub-littoral zone. Marine algal flora in Nai lagoon is represented by tropical characteristics.